Aspectos cinéticos da degradação aeróbia e anaeróbia de Cyperus giganteus, Eichhornia azurea e Egeria najas da lagoa do Óleo (Estação Ecológica de Jataí, Luiz Antônio, SP) - Gimenes, Karen Zauner (2011)
This study aimed to assess the effects of temperature on different aspects of aerobic and anaerobic degradation of aquatic macrophytes from different ecological groups: Cyperus giganteus (emergent), Eichhornia azurea (fixed floating) and Egeria najas (submerged). Considering these purposes, the carbon balance and mass decay, the cellulase and peroxidase activity in the degradation of cellulose and lignin, the oxygen consumption, as well as changes in pH, conductivity and humification degree caused by decomposition in the environment were analysed. In laboratory, decomposition chambers containing aquatic macrophyte and water samples were prepared and maintained under controlled conditions according to the experimental design. The results showed that: (i) temperature changes affected the mass loss coefficients of labile/soluble fractions of debris, but did not alter the mass loss coefficients of refractory fraction; (ii) the temperature increase accelerated the cellulose decay of E. azurea and E. najas detritus, being indifferent to those of C. giganteus; increased the lignin decay of C. giganteus and E. najas debris, although there was no lignin degradation of E. azurea within the experimental period; increased the peroxidase activity of the three species selected detritus and of the cellulase of C. giganteus and E. najas detritus, having the opposite effect on E. azurea debris; led to an increase in oxygen consumption in C. giganteus and E. azurea debris decomposition, having the opposite effect on E. najas decomposition; (iii) regardless to temperature, the content of particulate organic carbon and the half-life times were lower for submerged species and higher for the emerging one, which showed the highest contents of cellulose and lignin; (iv) the E. najas decomposition presented the highest dissolved oxygen consumption in the shortest time; (v) the mass loss of macrophytes detritus were faster under aerobic than under anaerobic condition.